Open and Closed Endotracheal Suctioning and Arterial Blood Gas Values: A Single-Blind Crossover Randomized Clinical Trial - Azam Faraji; Alireza Khatony; Gholamreza Moradi; Alireza Abdi; Mansour Rezaei (Critical Care Research and Practice)
Aim. This study was aimed at comparing the effects of the open and closed suctioning techniques on the arterial blood gas values in patients undergoing open-heart surgery. Methods. In a clinical trial, we recruited 42 patients after open-heart surgery in an educational hospital. Each patient randomly underwent both open and closed suctioning. ABGs, PaO2, SaO2, PaCO2, were analyzed before and one, five, and fifteen minutes after each suctioning episode. Results. At first the pressure of oxygen in arterial blood increased; however, this increase in the open technique was greater than that of the closed system (P<0.001). The pressure of oxygen decreased five and fifteen minutes after both suctioning techniques (P<0.05). The trends of carbon dioxide variations after the open and closed techniques were upward and downward, respectively. Moreover, the decrease in the level of oxygen saturation five and fifteen minutes after the open suctioning was greater than that of the closed suctioning technique (P<0.05).  Conclusion. Arterial blood gas disturbances in the closed suctioning technique were less than those of the open technique. Therefore, to eliminate the unwanted effects of endotracheal suctioning on the arterial blood gases, the closed suctioning technique is recommended.